Quad Band Handset Antenna for LTE MIMO and WLAN Application. (17th April 2014) - Wong, H. S.; Kibria, S.; Islam, M. T.; Mandeep, J. S.; Misran, N.
Abstract : A compact quad band antenna for long-term evolution (LTE) MIMO and WLAN application in the handset is presented in this paper. The proposed antenna comprises two symmetrical quarter wavelength radiating strips and a slotted ground plane. On the ground plane, a T-shaped slot is cut from the bottom. Two symmetrical P-shaped slots are etched at both sides of the ground plane. The radiating strips and slots generate a lower resonant at 780 MHz and an upper resonant at 2.350 GHz to cover LTE 700 Band 14, LTE 2300, 2.4 GHz WLAN, and LTE 2500. A novel isolation technique by placing a rectangular patch between the radiating strips is presented. The rectangular patch creates a dedicated current path for each radiating strip. The proposed antenna has high isolation of less than −18 dBi at LTE 2300, 2.4 GHz WLAN, and LTE 2500 band.